1998
DOI: 10.1103/physrevlett.81.104
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Electron Ponderomotive Blowout and Relativistic Self-Focusing by the Occurrence of Raman Scattering and Plasma Heating

Abstract: We use a fully explicit particle-in-cell model to demonstrate that electron blowout/cavitation and relativistic self-focusing can be prevented by the occurrence of stimulated Raman scattering and plasma heating. The suppression results predominantly from the scattering of laser power out of the focal cone and from the decrease in the plasma fluid's quiver velocity when the plasma is heated to multi-MeV temperatures. [S0031-9007(98)06445-X]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 22 publications
0
42
0
Order By: Relevance
“…Also, because there are a number of plasma periods (t p 2p͞v p ) within the pulse envelope, various instabilities such as Raman processes and laser-envelope modulations can cause laser beam breakup [10,11] and complicate the interpretation of the origin of electron acceleration [9,[12][13][14]. For instance, a recent analysis shows that the occurrence of Raman scattering and plasma heating will suppress both ponderomotive expulsion and RSF [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, because there are a number of plasma periods (t p 2p͞v p ) within the pulse envelope, various instabilities such as Raman processes and laser-envelope modulations can cause laser beam breakup [10,11] and complicate the interpretation of the origin of electron acceleration [9,[12][13][14]. For instance, a recent analysis shows that the occurrence of Raman scattering and plasma heating will suppress both ponderomotive expulsion and RSF [15].…”
mentioning
confidence: 99%
“…For ultrashort high-intensity pulses (t ϳ t p ), the physics may be significantly different and simpler, in that Raman scattering may not be important [15][16][17]. However, no experimental results have yet been presented, due to the difficulty in producing high-intensity pulses with such short pulse durations.…”
mentioning
confidence: 99%
“…[13][14][15] Tzeng et al 13 have shown that the plasma temperature can suppress the relativistic self-focusing of laser; Bergman and Eliasson 14 have studied the plasma dispersion relation in high temperature plasma; Li et al 15 have investigated the effect of plasma temperature on laser hosing instability. In these cases, the thermal velocity is comparable to the quiver velocity of the electrons in the laser fields and the electron mass is modulated by its thermal velocity too.…”
Section: Introductionmentioning
confidence: 99%
“…In the 2D slab geometry, P c is reduced by a factor √ 2 [33,34] , F es is enhanced by a factor 2, and F p ê r a 2 0 y r 2 0 exp(−2y 2 /r 2 0 ), where the laser vector potential has been taken as Equation (1). Then, one can rewrite Equations (11) and (12) in the 2D slab geometry as …”
Section: Upper-limit Laser Power and Lower-limit Plasma Densitymentioning
confidence: 99%
“…The extreme light infrastructure (ELI) will be able to provide hundredsof PW laser beams Correspondence to: Wei-Min Wang, Institute of Physics, CAS, P. O. Box 603 (33), Beijing 100190, China. Email: hbwwm1@iphy.ac.cn with intensity as high as 10 22 -10 25 Wcm −2 .…”
Section: Introductionmentioning
confidence: 99%